Interaction between healthcare professionals and parents is a key determinant of parental distress during childhood hospitalisation for respiratory syncytial virus infection (European RSV Outcomes Study [EROS]). (12th February 2018) - Carbonell‐Estrany, Xavier; Dall'Agnola, Alberto; Fullarton, John R.; Rodgers‐Gray, Barry S.; Girardi, Elisa; Mussa, Alessandro; Paniagua, Natalia; Pieretto, Marta; Rodríguez‐Fernandez, Rosa; Manzoni, Paolo
Abstract: Aim: We characterised the distress that parents experienced when their child was hospitalised for respiratory syncytial virus (RSV) infection. Methods: This survey‐based, observational study was conducted during 2014–2015. Meetings were held in Spain and Italy, with 24 parents of RSV hospitalised infants and 11 healthcare professionals experienced in RSV, which identified 110 factors related to parental distress. The resulting questionnaire was completed by another 105 Spanish and Italian parents and 56 healthcare professionals, to assess the impact these factors had on parental distress, using a scale from 0 to 10 (very unimportant to very important). Results: The five most important factors for parents were: healthcare professionals' awareness of the latest developments, readmission, reinfections, painful procedures and positive experiences with healthcare professionals. Healthcare professionals associated only medical factors with a meaningful impact on parents. Half of the six medical factors were given similar importance by both groups and the overall scoring for the 110 factors was comparable, with a correlation coefficient of 0.80. A primary concern on discharge was ongoing support. Conclusion: The relationship between parents and healthcare professionals was a significant factor in determining parental distress. Healthcare professionals appeared to have a good understanding of the overall impact on parents, particularly the key medical factors.